Toward a dual process model of moral injury and traumatic illness - Barr, Nicholas; Atuel, Hazel; Saba, Shaddy; Castro, Carl A. (Frontiers in Psychiatry, 2022)
Moral injury has emerged as a topic of significant research and clinical interest over the last decade. However, much work remains to be done to comprehensively define the moral injury construct, with implications for understanding the etiology and maintenance of moral injury, its symptoms, associations with and distinctions from traumatic illness, and treatment approaches. We provide a brief overview of the existing moral injury literature and introduce a novel dual process model (DPM) of moral injury and traumatic illness. The DPM posits an event exposure which may satisfy DSM-5 posttraumatic stress disorder (PTSD) criterion A, potential morally injurious event (PMIE) criteria, or both, followed by individual role appraisal as a perpetrator through action or inaction, a witness, a victim, or a combination of the these. Role appraisal influences symptoms and processes across biological, psychological, behavioral, social, spiritual/religious, as well as values, character, and identity domains to support a label of traumatic illness, moral injury, or both. The DPM provides a flexible analytical framework for evaluating symptoms associated with moral injury and traumatic stress and has important implications for treatment. The most thoroughly reviewed evidence-based interventions for traumatic stress hinge on exposure and habituation mechanisms to manage dysregulation of fear and memory systems, but these mechanisms often do not address core domains of moral injury identified in the DPM, including spiritual, religious, values, character, and identity domains as these exist largely outside of the putative fear network. We provide brief vignettes to illustrate the practical application of the DPM and argue that adjunct and stand-alone approaches which address values and character domains, leveraging principles of Stoicism, nonjudgment of experience, acceptance, and values-oriented action, are more likely than traditional trauma treatment approaches to positively affect moral injury symptoms.